Pengaruh Konten Online Terhadap Niat Perilaku Wisatawan pada Wisata Solo Safari yang Dimediasi oleh Kepuasan dan Interaksi Pemasaran Digital - Galih Ratnaning Tyas; Soepatini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effect of online content on tourist behavior intention at Solo Safari, mediated by satisfaction and digital marketing interaction. The research method used is a quantitative causal approach with primary data collected through online questionnaires distributed to tourists who visited Solo Safari in the past 3 months and interacted with posts on Instagram. The sample was selected using purposive sampling, and the number of respondents was calculated between 125 to 250 individuals. Data analysis was performed using Structural Equation Modeling (SEM) with SmartPLS 3 software. The results show that online content positively and significantly influences satisfaction, revisit intention, digital marketing interaction, and E-WOM, both directly and through satisfaction as a mediator. The study suggests focusing on content that enhances visitor satisfaction and improving the questionnaire design in future research.